The impact of achievement emotions on learning performance in online learning context: a meta-analysis - Qi, Mengmeng; Liu, Wenying; Li, Mingyue; Wang, Gaoge; Liu, Bowen (Frontiers in Psychology, 2025)
IntroductionIn online learning context, achievement emotions are of great significance and exert an influence on students’ learning performance. However, the research conclusions about the impact of achievement emotions on learning performance are not uniform.MethodsFollowing PRISMA guidelines, we searched Web of Science, Scopus, EBSCO and Google Scholar (2012–2024). 21 studies (240 independent effect sizes) met inclusion criteria and were analyzed with a random-effects model. Moreover, multiple moderating variables were investigated in the models, such as learner levels, disciplines, online learning styles, technological types, and types of performance measure.ResultsPositive emotions showed a moderate positive correlation with online learning performance (r = 0.478), whereas negative emotions showed a moderate negative correlation (r = –0.303). Technology type and performance-measure type significantly moderated these relationships, while learner level, discipline, and online learning style did not.DiscussionFindings underscore the importance of fostering positive emotions in online learning and of adopting technologies that lessen the detrimental influence of negative emotions. Implications for instructional design and future research are discussed.